Heavy metal (Zn, Pb, Cd) concentration in soil and moss (Pleurozium schreberii) in the Brynica district, southern Poland - Pajak M; Jasik M (iForest - Biogeosciences and Forestry, 2011)
The atmospheric heavy metal pollution (lead, cadmium and zinc) of the Brynica district (one of the most polluted regions of Poland) was assessed in the top layer of soils (0-20 cm), organic layer and in tissues of the common woodland moss Pleurozium schreberii. Samples were taken in July 2008 at 31 points distributed over a 1500 x 1500 m grid. The concentration of trace elements changed depending on analysed material, distance from the metallurgic complex “Miasteczko Slaskie” and type of metals. The highest concentrations were close to Miasteczko Slaskie. The highest values were in the organic layer. Moss samples were useful as biomonitors. The analyses confirmed a considerable contamination with heavy metals of the forest environment in the Brynica district.